2020
DOI: 10.3390/w12030868
|View full text |Cite
|
Sign up to set email alerts
|

Amendment of Husk Biochar on Accumulation and Chemical Form of Cadmium in Lettuce and Pak-Choi Grown in Contaminated Soil

Abstract: (1) Background: Cadmium (Cd) accumulated in vegetables not only affects their growth but can also enter the human body via food chains and lead to various illnesses. Plants can decrease the toxicity by changing the chemical forms of Cd, which include inorganic (FE), water-soluble (FW), pectate- and protein-integrated (FNaCl), undissolved phosphate (FHAc), oxalate (FHCl), and residual forms (FR). Among them, FE and FW chemical forms show higher mobility to translocate upward from roots to shoots compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Sweet (coded as LSS). The experimental results of the previous study showed that the LSC and LSS accumulated 2.1–6.9 and 1.8–3.1 mg kg −1 of Cd in the shoots after being grown for 35–49 d; moreover, the BCC and BCW accumulated 2.9–12.7 and 6.6–32.3 mg kg −1 of Cd in the shoots after being grown in the same Cd-contaminated soils for 35–49 d [ 43 ]. The two varieties of pak choi used in this study had higher accumulating capacity of Cd compared with the two lettuce cultivars.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sweet (coded as LSS). The experimental results of the previous study showed that the LSC and LSS accumulated 2.1–6.9 and 1.8–3.1 mg kg −1 of Cd in the shoots after being grown for 35–49 d; moreover, the BCC and BCW accumulated 2.9–12.7 and 6.6–32.3 mg kg −1 of Cd in the shoots after being grown in the same Cd-contaminated soils for 35–49 d [ 43 ]. The two varieties of pak choi used in this study had higher accumulating capacity of Cd compared with the two lettuce cultivars.…”
Section: Methodsmentioning
confidence: 99%
“…Another index translocation factor (TF)—the ratio of TM concentration in the shoot of a plant to that in the root of the plant—was used to examine the upward transport of TMs under different treatments. The hazard quotient (HQ v ) was calculated in accordance with Chen et al [ 43 ] to assess the health risk of TM through oral ingestion of vegetables using Equation (1), where C p is the TM concentration (mg kg −1 ) in the edible parts of the four leafy vegetables, MIDVC is the mean individual daily vegetable consumption (kg d −1 ), and TDI v is the tolerable daily intakes through oral ingestion of vegetables (mg kg −1 -BW d −1 ). Based on the Nutrition and Health Survey report and vegetable calorie counts, the MIDVC in Taiwan during 2013–2016 was 0.133 kg d −1 [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochar from rice husk was applied into a cadmium (Cd) contaminated soil by Chen et al [7]. Lettuce (Lactuca sative) and pak-choi (Brassica chinensis) were planted in the biochar-amended soil to observe the accumulation, translocation, and chemical forms of Cd in the leafy vegetables.…”
Section: Overview Of This Special Issuementioning
confidence: 99%